2022
DOI: 10.3390/app12052457
|View full text |Cite
|
Sign up to set email alerts
|

A Potential “Vitaminic Strategy” against Caries and Halitosis

Abstract: Streptococcus mutans and Fusobacterium nucleatum are two key bacteria of the oral microbiota. Due to their ability to form biofilms on oral tissues, they are both involved in the onset of the most common oral diseases. F. nucleatum is also the principal producer of hydrogen sulfide (H2S), causative of the awkward bad breath of halitosis. In this study, the oral product Vea® Oris, made by vitamin E and capric/caprylic acid only, was evaluated as a potential treatment for the most common oral diseases. Different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Specifically for halitosis-causing bacteria, THK-30 produces H 2 O 2 and bacteriocins. In previous studies, this has shown the inhibition of F. nucleatum , with one of the papers being under review [ 36 , 37 , 38 ]. The F. nucleatum -inhibiting mechanism of THK-30 relies on H 2 O 2 and bacteriocins to prevent the production of protease in F. nucleatum [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically for halitosis-causing bacteria, THK-30 produces H 2 O 2 and bacteriocins. In previous studies, this has shown the inhibition of F. nucleatum , with one of the papers being under review [ 36 , 37 , 38 ]. The F. nucleatum -inhibiting mechanism of THK-30 relies on H 2 O 2 and bacteriocins to prevent the production of protease in F. nucleatum [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The F. nucleatum -inhibiting mechanism of THK-30 relies on H 2 O 2 and bacteriocins to prevent the production of protease in F. nucleatum [ 39 ]. This effect in turn prevents amino acids from locking with their complex, preventing unpleasant VSC from being created [ 36 , 40 ]. Secondly, for the inhibition pathway, SHMP can capture biofilm components like calcium or phosphate of F. nucleatum and inhibit its survival ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the water-soluble ingredients are vitamin C and the complex of B vitamins, whose antioxidant effect neutralizes the reactive oxygen species (ROS) causative of many oral pathologies [40]. Vitamin C is the most common vitamin in kombucha, and its content in a single serving of kombucha varies within the reference daily intake (RDI).…”
Section: Introductionmentioning
confidence: 99%
“…Specific alterations in the composition of the salivary microbiome can be an indicator of different systemic conditions in the host [6,7]. Furthermore, different external factors such as oral hygiene and dietary habits can influence the oral microbiome [8,9]. Some treatments for metabolic disorders require patients to follow a specific diet or consume supplements.…”
Section: Introductionmentioning
confidence: 99%